2013
DOI: 10.3109/01676830.2013.764440
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Changes in Thyroid Eye Disease

Abstract: According to our results dry eye syndrome is present in 65.2% of patients (60.9% eyes) with TED. Significant risk factors of ocular surface damage in TED were exophthalmos, lagophthalmos, palpebral fissure height and lower lid retraction. Positive conjunctival staining results from punctuate epithelial erosions and excessive desquamation of superficial cells. Histopathologic changes detected in conjunctiva consistent with dry eye and are not specific for TED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 7 publications
1
36
0
4
Order By: Relevance
“…The lacrimal gland physiologically expresses the TSH receptor, which, in active GO, can bind with circulating anti-TSHR autoantibodies and contribute to lacrimal gland impairment [46]. This is an immune-mediated lacrimal gland dysfunction initially characterized by inflammation and followed by gland fibrosis and dropout, manifesting as a secondary Sjögren's syndrome in long-lasting disease [46,47,48,49,50]. Proteomics of tear fluids demonstrated an upregulation of inflammatory proteins and a downregulation of protective proteins in GO, with a significantly different panel compared to dry-eye patients and controls [51].…”
Section: Recommendationsmentioning
confidence: 99%
“…The lacrimal gland physiologically expresses the TSH receptor, which, in active GO, can bind with circulating anti-TSHR autoantibodies and contribute to lacrimal gland impairment [46]. This is an immune-mediated lacrimal gland dysfunction initially characterized by inflammation and followed by gland fibrosis and dropout, manifesting as a secondary Sjögren's syndrome in long-lasting disease [46,47,48,49,50]. Proteomics of tear fluids demonstrated an upregulation of inflammatory proteins and a downregulation of protective proteins in GO, with a significantly different panel compared to dry-eye patients and controls [51].…”
Section: Recommendationsmentioning
confidence: 99%
“…Similarly, Wei et al [61] performed histopathological analysis (in vivo confocal microscopy) of IC membranes from 15 TO subjects versus 15 controls, to investigate changes to the conjunctiva. As seen by Ismailova et al [60], Wei et al [61] noted reduced bulbar conjunctival goblet cell density (superior and temporal, p < 0.004 and p < 0.01, respectively), as well as significantly increased squamous metaplasia in the TO group (both superior and temporal, p < 0.001). Moreover, the latter study found significantly lower levels of superficial epithelial cell density in the superior bulbar conjunctiva, versus controls (p = 0.002).…”
Section: Thyroid Orbitopathymentioning
confidence: 70%
“…Moreover, the latter study found significantly lower levels of superficial epithelial cell density in the superior bulbar conjunctiva, versus controls (p = 0.002). Both studies appear to endorse the fact that IC can be used to confirm a clinical diagnosis of DED in patients with TO [60,61]. The question remains as to whether these findings are specific to TO and so this may be where the identification of other biomarkers of ocular surface inflammation, that are specific to the condition, comes into play.…”
Section: Thyroid Orbitopathymentioning
confidence: 87%
See 2 more Smart Citations